PEMODELAN DINAMIKA KENDARAAN OTONOM SKALA KECIL - Rusman Suwarno (Jurnal Online Sekolah Tinggi Teknologi Mandala, 2016)
Autonomous vehicles have been the subject of research for recent years. Most of the research are focused on the design and development of control algorithm for vehicle motion. However, dynamic modeling of autonomous vehicle is very important as they are designed to travel at high speed and to have good handling responses. This paper presents and discusses the dynamic modeling of a small scale vehicle to be used as autonomous vehicle in order to study the dynamic behavior of real autonomous vehicle. The dynamic model is developed based on the real scale vehicle and is simulated using parameter from the small scale vehicle. An instrumented experimental small scale vehicle with the corresponding parameter is developed and tested to obtain the dynamic behavior for some steering inputs. The results from the experiment are compared to the simulation results. The simulations results show a good agreement with the experimental results. Some handling parameters are estimated from the experiment.